Magnetic volume susceptbility of 12 gravity cores from RV MARIA S. MERIAN cruise MSM111 - Tilo von Dobeneck; Michal Kucera; Johan C Faust (PANGAEA, 2025)
All sediment series recovered during MERIAN Cruise MSM 111 by gravity coring were subject to routine magnetic susceptibility logging, which was performed on the closed full core segments. The magnetic volume susceptibility κ of marine sediment is primarily determined by its ferrimagnetic mineral content; paramagnetic matrix components such as clays are of minor relevance. As a dimensionless quantity, κ may vary from an absolute minimum value of -1510^-6 for diamagnetic minerals (such as water, pure carbonate or silicate) to a maximum of some 10·10^-3 for sediments rich in ferrimagnetic (titano-)magnetite (here mainly magmatic-sourced, ice-rafted or current-transported materials). The MARUM Multi-Sensor Core Logging System (MSCLS) is mounted with a commercial BARTINGTON M.S.2 susceptibility meter with a 140 mm loop sensor. Due to the sensor extquotesingles size, its sensitivity extends over a core interval of about 8 cm (half-width). Consequently, sharp susceptibility changes will appear smoothed in the κ core log and thin layers are not well resolved. In order to make an accurate segment end corrections and to assess the drift of the susceptibility meter, each core segment was measured separately. During post-processing, core top and bottom ends were mirror-corrected. The systematic decline of the susceptibility signal between segment boundaries was recovered by summing the overlapping tail data leading to loss-free data sets.